INSERLAB -Pathways to Inclusion through Work-Integrated Learning - Teresa TORRES-CORONAS (Communications of International Proceedings, 2024)
This paper presents a comprehensive analysis of a university training program aimed at enhancing the socio-labour integration of individuals with intellectual and developmental disabilities. The program employs a holistic methodology that incorporates work-integrated learning, personalized tutoring, and competency development. The results of this study indicate a significant positive impact on participants, notably improving their employability and dismantling social stereotypes about their capabilities in the workforce. Employers engaged in the program were more inclined to hire individuals with disabilities, highlighting the benefits of active participation and exposure. The implications of these findings reinforce the importance of lifelong learning and inclusive education policies in facilitating the labour integration of individuals with intellectual and developmental disabilities.
Keywords: Higher education; labour market active policies; intellectual and development disability; work-integrated learning.